Antifungal mechanisms of the antagonistic bacterium Bacillus mojavensis UTF-33 and its potential as a new biopesticide - Zhang, Yifan; Yang, Yanmei; Zhang, Luyi; Zhang, Jia; Zhou, Zhanmei; Yang, Jinchang; Hu, Yu; Gao, Xiaoling; Chen, Rongjun; Huang, Zhengjian; Xu, Zhengjun; Li, Lihua (Frontiers in Microbiology, 2023)
Biological control has gradually become the dominant means of controlling fungal disease over recent years. In this study, an endophytic strain of UTF-33 was isolated from acid mold (Rumex acetosa L.) leaves. Based on 16S rDNA gene sequence comparison, and biochemical and physiological characteristics, this strain was formally identified as Bacillus morgavsis. Bacillus mojavensis UTF-33 was sensitive to most of the antibiotics tested except neomycin. Moreover, the filtrate fermentation solution of Bacillus mojavensis UTF-33 had a significant inhibitory effect on the growth of rice blast and was used in field evaluation tests, which showed demonstrated the effective reduction of rice blast infestation. Rice treated with filtrate fermentation broth exhibited multiple defense mechanisms in response, including the enhanced expression of disease process-related genes and transcription factor genes, and significantly upregulated the gene expression of titin, salicylic acid pathway-related genes, and H2O2 accumulation, in plants; this may directly or indirectly act as an antagonist to pathogenic infestation. Further analysis revealed that the n-butanol crude extract of Bacillus mojavensis UTF-33 could retard or even inhibit conidial germination and prevent the formation of adherent cells both in vitro and in vivo. In addition, the amplification of functional genes for biocontrol using specific primers showed that Bacillus mojavensis UTF-33 expresses genes that can direct the synthesis of bioA, bmyB, fenB, ituD, srfAA and other substances; this information can help us determine the extraction direction and purification method for inhibitory substances at a later stage. In conclusion, this is the first study to identify Bacillus morgavsis as a potential agent for the control of rice diseases; this strain, and its bioactive substances, have the potential to be developed as biopesticides.